A quantificação da deformação em rochas metassedimentares dos grupos costa sena e guinda, Paleoproterozóico da Serra do Espinhaço meridional - Juni Silveira Cordeiro (2008)
Methodology of strain quantification like Rf/; Panozzo; Intercept method, main orientation of grains, Fry method; Center-to-Center and a like square minimum in 31 experimental figures help to choice the methods with best results in the strain analysis of quartzitics rocks of Serra do Espinhaço Meridional. The analysis of Rs (initial ratio of strain), R0 (initial ratio of objects) and the roundness of shapes shows that is necessary pay attention in the interpretation of results, especially when we have two deformation events (sedimentary or tectonic). We choice to use Rf/, Fry, Center-to-Center and in some samples Panozzo and SPO (Shape Preferred Orientation) to the strain quantification in 76 samples of quartzitics rocks of Diamantina Quadrangle 1:100.000, collected in outcrops of Costa Sena and Guinda groups in different stratigraphic and tectonics situations, with a more dense grid in the region of Guinda Quadrangle 1:25.000, SW of Diamantina and at the southern portion of Serra da Matriculada (Datas). The samples were oriented in the field and cuts done parallel to mineral elongation lineation (XZ plane) or orthogonal (YZ plane). The data analysis of the central region of Guinda Quadrangle shows mainly a greater deformation of matrix than the grains with Rs between 3.75 and 1.45 (XZ plane - Rf/), 2.71 and 1.29 (Fry traditional), 2.41 and 1.15 (Center-to-Center), 3.41 and 1.04 (Panozzo). The R0 from Rf/ shows high values (1.35 and 2.05 in XZ plane, 1.35 and 2.02 in YZ plane). In the Serra da Matriculada region we have a greater deformation of grains with Rs between 1.78 and 4.71 (Rf/) with an high R0 (1.36 to 2.13 in XZ plane and 1.30 to 2.44 in YZ plane). The Flinn parameter in both regions shows that almost all samples falls in a oblate ellipsoid (shortening field). The data suggests that the control of deformation is more associated with litologies than with the stratigraphy, greater in the micaceous types with greater strain near the trusts that are responsible for the stratigraphic inversions of the metasediments of Costa Sena and Guinda groups. In other hand, the samples of stratigraphic units with well preserved sedimentary structures, how in the east part of Guinda Quadrangle, show strain ratio compatible but light higher than suggested by sedimentary/diagenetics process. The strain quantification in 12 boulders of Bandeirinha Formation in the basal breccia of São João da Chapada Fm. shows high values but the orientation of principal axis suggested a deformation with the matrix and not an early deformation. The analysis of Anisotropic Magnetic Suscetibility of 4 samples of a ferruginous breccia with a well development axial plane foliation and a ferruginous quartzite, both of Caldeirões Member (Sopa-Brumadinho Fm.), show a good compatibility between these results and the traditional of strain quantification